1999
DOI: 10.1074/jbc.274.23.16028
|View full text |Cite
|
Sign up to set email alerts
|

Flux of the l-Serine Metabolism in Rabbit, Human, and Dog Livers

Abstract: L-Serine metabolism in rabbit, dog, and human livers was investigated, focusing on the relative contributions of the three pathways, one initiated by serine dehydratase, another by serine:pyruvate/alanine:glyoxylate aminotransferase (SPT/AGT), and the other involving serine hydroxymethyltransferase and the mitochondrial glycine cleavage enzyme system (GCS). Under quasi-physiological in vitro conditions (1 mM L-serine and 0.25 mM pyruvate), flux through serine dehydratase accounted for only traces, and that thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…SDS converts serine to pyruvate and ammonia (14). AGXT is also involved in the metabolism of pyruvate and serine (15). GOT1 is involved in the malate-aspartate shuttle and thereby in the production of oxaloacetate, which serve as substrates for gluconeogenesis via a PEPCK-mediated reaction (16).…”
Section: Resultsmentioning
confidence: 99%
“…SDS converts serine to pyruvate and ammonia (14). AGXT is also involved in the metabolism of pyruvate and serine (15). GOT1 is involved in the malate-aspartate shuttle and thereby in the production of oxaloacetate, which serve as substrates for gluconeogenesis via a PEPCK-mediated reaction (16).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that AGT also has serine:pyruvate aminotransferase activity, which although much lower than its alanine:glyoxylate aminotransferase activity might be important for its gluconeogenic role (28). In the present study, the serine:pyruvate aminotransferase activity of purified recombinant AGT-His, AGT (23,29).…”
Section: Expression and Purification Of His-tagged Agt-many Of The Agmentioning
confidence: 88%
“…SPT/AGT exhibits not only the AGT activity but also the SPT activity with both of these two activities being of physiological significance [7]. Assay of the AGT activity of SPT/AGT in human liver extract is associated with a problem that glutamate:glyoxylate aminotransferase (GGT) also catalyzes transamination between alanine and glyoxylate.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial production of glyoxylate from hydroxyproline is assumed to play a significant role in carnivores [5], because the hydroxyproline content of collagen reaches about 10–13% [6] and collagen accounts for about 30% of total animal protein. Although SPT/AGT is a bifunctional enzyme involved in the metabolism of both L -serine and glyoxylate, its contribution to L -serine metabolism is independent of mitochondrial or peroxisomal localization [7]. …”
Section: Introductionmentioning
confidence: 99%